HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN MASYARAKAT USIA PRODUKTIF DALAM PEMANFAATAN POS PEMBINAAN TERPADU PENYAKIT TIDAK MENULAR (POSBINDU PTM): RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND COMPLIANCE OF PRODUCTIVE AGE COMMUNITIES IN UTILIZING INTEGRATED COACHING POST OF NON-COMMUNICABLE DISEASES (POSBINDU PTM) - Purnamasari, Ni Kadek Ayu; Muliawati, Ni Kadek; Faidah, Nurul (Bali Medika Jurnal, 2020)
is a form of community participation in the early detection, monitoring and early follow-up of PTM risk factors independently and continuously. One of the factors influencing the low level of Posbindu PTM visits is the community's knowledge about the use of Posbindu PTM. If the public's knowledge is less about Posbindu PTM, it will result in an increase in mortality due to PTM. To analyze the relationship between the level of knowledge and the compliance of the productive age community in the use of Posbindu PTM. This study used a descriptive correlational method with a cross sectional approach conducted on 93 samples using a sampling technique that is non probability sampling with a purposive sampling technique. Results: Most of the productive age community in Busung Yeh Kauh had less knowledge level with less compliance level, as many as 50 people (53.8%). The Spearman Rank statistical test results obtained p = 0,000 (<0.05) with a correlation coefficient of 0.855 which means that there is a very strong relationship between the level of knowledge with the compliance of the productive age community in the use of Posbindu PTM. Public knowledge about Posbindu PTM influences compliance with the use of Posbindu PTM. Efforts should be made to increase public education about the importance of utilizing Posbindu non-communicable diseases to reduce mortality due to non-communicable diseases.